Social accounting matrices and multiplier analysis: An introduction with exercises - Breisinger, Clemens; Thomas, Marcelle; Thurlow, James (International Food Policy Research Institute, 2009)
This training guide introduces development practitioners, policy analysts, and students to social accounting matrices (SAMs) and their use in policy analysis. There are already a number of books that explain the System of National Accounts and SAM multipliers—some of these are recommended at the end of this training guide. However, most books tend to be quite technical and move quickly from an introduction to more complex applications. By contrast, this guidebook uses a series of hands-on exercises to gradually introduce SAMs and multiplier analysis. It therefore complements more theoretical SAM and multiplier literature and provides a first step for development practitioners and students wishing to understand the strengths and limitations of these economic tools. It is also useful for policy analysts and researchers embarking on more complex SAM-based methodologies. One such methodology is computable general equilibrium (CGE) modeling, for which IFPRI has also developed a series of introductory exercises and a standard modeling framework.